Evaluation of long-term sequelae by cardiopulmonary exercise testing 12 months after hospitalization for severe COVID-19 - Noureddine, Sofia; Roux-Claudé, Pauline; Laurent, Lucie; Ritter, Ophélie; Dolla, Pauline; Karaer, Sinan; Claudé, Frédéric; Eberst, Guillaume; Westeel, Virginie; Barnig, Cindy (BMC Pulmonary Medicine, 2023)
Background Cardiopulmonary exercise testing (CPET) is an important clinical tool that provides a global assessment of the respiratory, circulatory and metabolic responses to exercise which are not adequately reflected through the measurement of individual organ system function at rest. In the context of critical COVID-19, CPET is an ideal approach for assessing long term sequelae. Methods In this prospective single-center study, we performed CPET 12 months after symptom onset in 60 patients that had required intensive care unit treatment for a severe COVID-19 infection. Lung function at rest and chest computed tomography (CT) scan were also performed. Results Twelve months after severe COVID-19 pneumonia, dyspnea was the most frequently reported symptom although only a minority of patients had impaired respiratory function at rest. Mild ground-glass opacities, reticulations and bronchiectasis were the most common CT scan abnormalities. The majority of the patients (80%) had a peak O 2 uptake (V′O 2 ) considered within normal limits (median peak predicted O 2 uptake (V′O 2 ) of 98% [87.2–106.3]). Length of ICU stay remained an independent predictor of V′O 2 . More than half of the patients with a normal peak predicted V′O 2 showed ventilatory inefficiency during exercise with an abnormal increase of physiological dead space ventilation (VD/Vt) (median VD/VT of 0.27 [0.21–0.32] at anaerobic threshold (AT) and 0.29 [0.25–0.34] at peak) and a widened median peak alveolar-arterial gradient for O 2 (35.2 mmHg [31.2–44.8]. Peak PetCO 2 was significantly lower in subjects with an abnormal increase of VD/Vt ( p = 0.001). Impairments were more pronounced in patients with dyspnea. Peak VD/Vt values were positively correlated with peak D-Dimer plasma concentrations from blood samples collected during ICU stay (r 2 = 0.12; p = 0.02) and to predicted diffusion capacity of the lung for carbon monoxide (D LCO ) (r 2 =  − 0.15; p = 0.01). Conclusions Twelve months after severe COVID-19 pneumonia, most of the patients had a peak V′O 2 considered within normal limits but showed ventilatory inefficiency during exercise with increased dead space ventilation that was more pronounced in patients with persistent dyspnea. Trial registration : NCT04519320 (19/08/2020).